DIAGNOSA HUBUNGAN PENGETAHUAN AWAL (PRIOR KNOWLEDGE) TERHADAP KESULITAN BELAJAR SISWA PADA MATERI LARUTAN PENYANGGA DI SMA N 1 SOLOK - Andriani, Novi (journal of residu, 2019)
Buffer solution is one of the lessons that are considered difficult by students. This is because in learning the buffer solution has a lot of prior knowledge, which must be understood by students in order to understand the buffer solution. This research means to analyze the relationship of prior knowledge with students' learning difficult in learning buffer solutions in SMA N 1Solok. This research is a descriptive study conducted on class XI students of SMA N 1 Solok. The research subjects were 47 students. Data analysis techniques are carried out quantitative means at determining the percentage of students' learning difficulties in learning buffer solutions and the percentage of learning difficulties in the prior knowledge. From the research found the percentage of students experiencing learning difficulties with a very high category, namely the subject matter of the capacity of the buffer solution 92.3% and the pH of the buffer solution 83%, then the percentage with a high category on the subject matter of the mechanism of the buffer solution is 74.5%, and the moderate category in the material the properties of the buffer solution is 65.3%.  Learning difficulties by students are caused students do not understand the prior knowledge which is a prerequisite for learning buffer solutions in the form of chemical equilibrium, equilibrium constants, Brownsted-Lowry acid base concepts and acid base stoichiometry.   Keyword:  Prior Knowledge, Learning Difficulties, Buffer Solution